Analisis Peran Fonologi dalam Membentuk Kejelasan Bahasa Indonesia di SD - Nia Raudhatul Aulya; Silvina Noviyanti; Nazurty; Anissa Maysaroh; Dini Nursabila; Sania (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT This study aims to describe the role of phonology in forming the clarity of Indonesian language. Phonology, as a branch of linguistics that studies the sound system of language, plays an important role in supporting speech comprehensibility through accurate pronunciation of phonemes, articulation, intonation, stress, and pauses. This research uses a literature review method by examining relevant sources such as books, scholarly journals, and language-related articles. The findings indicate that the clarity of Indonesian language is strongly influenced by speakers’ ability to produce speech sounds accurately according to linguistic rules. Pronunciation errors may cause ambiguity and reduce communication effectiveness. In addition, phonology also contributes to Indonesian language learning because it forms the basis for developing speaking and listening skills. Therefore, mastery of phonology is essential to support clear, accurate, and effective communication in the use of Indonesian language. Keywords: phonology, language clarity, Indonesian language, oral communication, literature review